Identification of seven serum microRNAs from a genome‐wide serum microRNA expression profile as potential noninvasive biomarkers for malignant astrocytomas. Issue 1 (26th June 2012) - Yang, Cuihua; Wang, Cheng; Chen, Xi; Chen, Sidi; Zhang, Yanni; Zhi, Feng; Wang, Junjun; Li, Limin; Zhou, Xiaojun; Li, Nanyun; Pan, Hao; Zhang, Junfeng; et al.
Abstract The involvement of circulating microRNAs (miRNAs) in cancer and their potential as biomarkers of diagnosis and prognosis are becoming increasingly appreciated; however, little is known about circulating miRNA profiles in astrocytomas. In our study, we performed genome‐wide serum miRNA analysis by the Solexa sequencing followed by validation conducted in the training and verification sets with a stem‐loop quantitative reverse‐transcription PCR (RT‐qPCR) assay from serum samples of 122 untreated astrocytomas patients (WHO grades III–IV) and 123 normal controls. Identified miRNAs were subsequently examined in 55 grade II, 15 grade I astrocytomas, 11 astrogliosis, 42 other primary brain tumors and 8 tumor tissues from grades II–IV astrocytomas. In addition, paired serum samples before and after operation were collected from 14 malignant astrocytomas to determine the effect of surgery on the miRNAs' levels. A marked difference in serum miRNA profile was observed between high‐grade astrocytomas and normal controls. Seven miRNAs were validated by RT‐qPCR assay to be significantly decreased in grades II–IV patients (p < 0.001), including miR‐15b*, miR‐23a, miR‐133a, miR‐150*, miR‐197, miR‐497 and miR‐548b‐5p, and the seven‐miRNA panel demonstrated a high sensitivity (88.00%) and specificity (97.87%) for malignant astrocytomas prediction. These identified miRNAs also exhibited a global decrease in tumor tissues relative to normal tissues. Furthermore, these miRNAs in serum were markedly elevated after operation (p < 0.001). In addition, some of these serum miRNAs were significantly different between malignant and benign cases, astrogliosis and other primary brain tumors. The seven serum miRNAs identified in our study hold potential as noninvasive biomarker for malignant astrocytomas.